2013
DOI: 10.1037/a0031764
|View full text |Cite
|
Sign up to set email alerts
|

Boosting workplace stair utilization: A study of incremental reinforcement.

Abstract: This study supports that stair usage in the workplace is a viable way to increase physical activity. This study adds to existing research that attempted to increase stair utilization through promotion only by adding a behavioral reinforcement strategy. Finally, this study demonstrates that a physical activity among employees at the worksite can be increased with minimal relative cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Likewise, the Patient Protection and Affordable Care Act (PPACA, effective as of January 1 st , 2014) encourages the use of incentive programs to improve preventative care (62). Consistent with the PPACA, several uncontrolled studies have demonstrated favorable results for incentivized worksite physical activity programs (36, 3941). Offering cash rebates of $150 (40) or savings on out-of-pocket insurance expenses (up to $2000 in some cases) (41) have yielded pre-post increases in both self-reported and objectively measured physical activity behavior, respectively.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Likewise, the Patient Protection and Affordable Care Act (PPACA, effective as of January 1 st , 2014) encourages the use of incentive programs to improve preventative care (62). Consistent with the PPACA, several uncontrolled studies have demonstrated favorable results for incentivized worksite physical activity programs (36, 3941). Offering cash rebates of $150 (40) or savings on out-of-pocket insurance expenses (up to $2000 in some cases) (41) have yielded pre-post increases in both self-reported and objectively measured physical activity behavior, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…One option is the use of substantially smaller monetary incentives to influence exercise behavior. For example, in an uncontrolled intervention study, Schummacher and colleagues (36) demonstrated that relatively minimal incentives ($0.20 per day maximum) boosted employee stair utilization within a larger employee-based health rewards program. A second option is implementing a negative reinforcement “buy-in” system, in which participants pay a fee to enroll that provides an opportunity to earn money back for meeting exercise goals.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies were web- or mHealth-based, 108119 eight were implemented in educational settings, 120126 five were conducted in laboratory settings, 106,127130 and four were implemented in sports facilities. 131134 Other studies reported interventions conducted at the workplace, 135137 in medical centres, 114,138 in a senior centre, 130 or outdoors. 139 Participants were employees ( n = 7), 113117,119,120,131,135137 college students ( n = 8) 106,111,124,127,128,131,134 and school children ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in line with Soler et al (80), finding strong evidence that point-of-decision prompts can increase the proportion of people choosing stairs instead of the elevator or escalator. In our review, a majority of the interventions used point-of-decision prompts, but positive effects on PA were also observed in those 3 studies including environmental changes (61, 66, and 68) and 1 using financial incentives (65).…”
Section: Interventions Promoting Stair Usementioning
confidence: 99%